The Importance of New Managerial Quality Evaluation Visa-vis in the Millennial Era - Amanor, Christina (International Journal of Economics and Business Management, 2025)
The millennial era marked by technological developments, changes in social values, and rapid market dynamics demands a more adaptive and innovative managerial approach. Evaluation of new managerial qualities is important to ensure that leadership and management practices can meet the needs of the millennial generation who tend to be more collaborative, flexible, and goal-oriented. Evaluation of new managerial qualities is not only important to adapt to the characteristics of the millennial generation, but also becomes the key to organizational success in facing challenges in the digital era. This article has examined a few of the different viewpoints of Human Asset Administration counting, human asset arranging, choice and enrollment of staff, work examination and individual detail.